ENDURING CLIMATE CHANGE AND FOOD INSECURITY THROUGH CHARCOAL PRODUCTION: A POVERTY COPING STRATEGY OF RELUCTANTINDIGENOUS WOMEN IN THE PHILIPPINES - Susanita G. Lumbo (Lembaga Penelitian Universitas Pasundan, 2017)
This case study looked into the Philippines’ indigenous women’s understanding of charcoal production and its connection to climate change. This specifically determined their level of knowledge of and attitude towards climate change and perception on the effects of climate change on health, livelihood, and environment. The study employed triangulation method consisting of household interview, field observation, and key informant interview. Twenty-four women belonging to Hanunuo and Ratagnon Mangyan tribes served as participants of the study. They were fairly young, married, lowly educated, and had bigger households. Their primary sources of income included slash-and-burn farming and charcoal making. Their monthly family income fell below the poverty threshold. The women were reluctant charcoal makers pushed to the limits due to lack of economic options. They had “very high” knowledge about climate change but had “neutral” attitude towards it. They agreed charcoal production contributes to climate change. They already felt the phenomenon’s manifest effects on their health, livelihood, and environment. However, they needed to endure these while they cope with poverty and food insecurity. They lamented charcoal production is their only available option for their survival as upland farming is no longer viable. They hoped they can avail of livelihood options, which do not entail extraction of natural resources.